2019
DOI: 10.1007/s40201-019-00373-y
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content and health risk assessment of commonly patronized herbal medicinal preparations from the Kumasi metropolis of Ghana

Abstract: Purpose To address the question of whether users of herbal products (HPs) are exposed to harmful contaminants, we evaluated six HPs mostly patronized in Kumasi for heavy metal contamination and assessed the health risk associated with their use. This study is one of the first safety evaluation studies on finished multiherbal products in the region. Method Three antimalarial, two antidiabetic and one antihypertensive HPs were selected after a mini-survey and coded randomly as HP A-F. The HPs were acid digested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
5
30
1
Order By: Relevance
“…This assertion on HPC also correlates well with a clinical trial of the same product which was published at the time this current study was ongoing [34]. On the other hand, the argument for a possible chronic liver toxicity induced by the HPs is supported by the previously identified chemical toxicants in these products [20,35]. Histologic findings from this study, however, support the induction of liver toxicity by the HMPs.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This assertion on HPC also correlates well with a clinical trial of the same product which was published at the time this current study was ongoing [34]. On the other hand, the argument for a possible chronic liver toxicity induced by the HPs is supported by the previously identified chemical toxicants in these products [20,35]. Histologic findings from this study, however, support the induction of liver toxicity by the HMPs.…”
Section: Discussionsupporting
confidence: 86%
“…The induction of GIT lesions by HPB seems to correlate with our recent study where we reported the presence of significantly high levels of Cr above MRL limit in this herbal preparation [20]. Similar morphological changes were observed in the lungs of rats that received HPC with the alveolar showing inflammatory changes dominated by lymphocytes and macrophages and alveolar spaces obscured by debris and chronic inflammatory cells which could be attributed to the heavy metal contaminations previously identified at concentrations above their respective MRL values [20,37].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations